APLIKASI BIOCHAR SEKAM PADI DAN BAKTERI PELARUT FOSFAT Paenibacillus sp. PADA TANAMAN CABAI MERAH (Capsicum annum L) DI MEDIUM ULTISOL - Beatrix Stella Marien Simamora; Zulfatri; Armaini (UIR Press, 2021)
Red chili is a commodity that must be developed in the Riau, which is mostly ultisol soil. Rice husk biochar as an ameliorant can increase plant growth. Also the bacteria Paenibacillus sp. can solubilize unavailable phosphate to become available for red chili plants. This study aimed to know the best doses between the combination of rice husk biochar and phosphate solubilizing bacteria Paenibacillus sp. on the growth of red chili plants. The study was conducted at the experimental farm of the Faculty of Agriculture, the University of Riau from January to May 2021, using non-factorial and randomized completely design, then tested with Duncan's new multiple range test (DNMRT). The combination factor is rice husk biochar and phosphate solubilizing bacteria Paenibacillus sp.: 0 g/polybag + 0 ml (B1); 0 g/polybag + 15 ml (B2); 0 g/polybag + 30 ml (B3); 0 g/polybag+ 45 ml (B4); 210 g/polybag + 0 ml (B5); 210 g/polybag + 15 ml (B6); 210 g/polybag + 30 ml (B7); 210 g/polybag + 45 ml (B8); 420 g/polybag + 0 ml (B9); 420 g/polybag + 15 ml (B10); 420 g/polybag + 30 ml (B11); and 420 g/polybag + 45 ml (B12). Parameters observed were plant height, stem diameter, number of branches, number of leaves, leaf width, number of flowers, and root dry weight. The results showed that the combination of 420 g/polybag rice husk biochar and 45 ml bacteria Paenibacillus sp. affected both the vegetative and generative growth of red chili plants.